IMPLEMENTASI NILAI-NILAI KARAKTER ISLAM OLEH GURU AKIDAH AKHLAK DALAM MENANGKAL PERILAKU MENYIMPANG SISWA MADRASAH TSANAWIYAH MAZNIYAH KOTA JAMBI - Atiqoh Dianti; Sururudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the gap between the role of Akidah Akhlak teachers in instilling Islamic character values and the reality of deviant behavior still found among students at MTs Mazniyah Kota Jambi. This study aimed to describe the implementation of Islamic character values by Akidah Akhlak teachers, identify the forms of students' deviant behavior, and analyze the supporting and inhibiting factors. This research employed a qualitative approach with a descriptive design. The subjects consisted of the Akidah Akhlak teacher as the main informant, along with the head of madrasah, homeroom teacher, guidance counselor, and students as supporting informants, selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed inductively through data reduction, data display, and conclusion drawing, and validated through triangulation. The findings show that the implementation of Islamic character values-religiosity, honesty, discipline, responsibility, and social care-was carried out through learning, habituation, exemplary conduct, and religious activities such as Qur'an recitation and congregational prayers. The Akidah Akhlak teacher functioned as educator, mentor, motivator, and role model (uswatun hasanah). Supporting factors included the head of madrasah's leadership and a structured religious culture, while inhibiting factors stemmed from negative peer influence, uncontrolled social media use, and insufficient family supervision.